Administrative Warnings as an Environmental Prevention Instrument at the Urban Community Level - Taufiq Supriadi; Nico Nico; Dianty Savitri; Naufal Afra Munis (Journal Research of Social Science, Economics, and Management, 2026)
Environmental damage in urban areas is not always caused by large-scale environmental crimes, but often stems from repeated and neglected minor administrative violations. Administrative reprimands are one of the strategic initial instruments in preventing the escalation of environmental damage without having to resort to a criminal approach. This study aims to analyze the role and effectiveness of administrative reprimands as a community-based environmental prevention instrument at RT 8 RW 4 Malaka Jaya, East Jakarta. A normative juridical approach combined with a light empirical approach through field observation was employed. Data were collected through library research, non-participatory observation over two months (January-February 2025), and documentation. The findings show that verbal reprimands were effective in 83.3% of cases, while written reprimands were effective in 60% of cases. The dominant violations were improper waste disposal (48.9%), open waste burning (17.0%), and neglected waterway cleanliness (14.9%). Key success factors include social closeness between RT administrators and residents, a persuasive and familial approach, consistent application, collective agreements, and community supervision. However, normative gaps were identified in legal legitimacy, documentation systems, and capacity building for RT administrators. This study confirms that administrative reprimands have significant preventive value if supported by community participation. Strengthening written guidelines, documentation systems, and legal capacity for RT administrators is recommended.